(untitled) (Mongolian Journal of Agricultural Sciences, 2019)
The small ruminant lentivirus (SRLV) is not identified in Mongolia despite the seroprevalence studies in last years. The reason for the virus identification might be the high diversity of viral strains in different geographical regions, healthy appearance of some infected animals, slow progression of the disease, low number of infected cells in peripheral blood, insensitivity of the diagnostics etc. We determined the seroprevalence of 12% for SRLV in central regions (Tov, Selenge, Bulgan) during 2016-2018. The lung of some seropositive sheep’s with clinical symptoms showed macroscopically and microscopically typical characteristics for SRLV infection, namely enlarged lung lobes with chronic inflammations. Two positive samples resulted out of fifty blood and eight lung samples in proviral gag specific polymerase chain reaction of the SRLV. The nucleotide sequence of the 536 bp PCR product evaluated as small ruminant lentivirus which is the first identified in Mongolia. Бог малын лентивирус илрүүлсэн дүнгээс Хураангуй: Адууны халдварт цус багадах өвчин (АХЦБӨ), Бог малын лентивирус(БМЛВ) -ээр үүсгэгддэг халдварт өвчнүүд манай оронд өргөн тархалттай байгаа нь серологийн шинжилгээгээр тогтоогдсон байна. Гэвч вирусийг өнөөг хүртэл илрүүлэн тодорхойлоогүй байгаа нь вирусийн халдварыг үнэн зөв оношлох, эрт илрүүлэн тэмцэх арга хэмжээг зохион байгуулахад учир дутагдалтай байгаа юм. Бид Төвийн бүсийн (БМЛВ)-ийн халдварыг шинэчлэн тогтоохын зэрэгцээ (12%), өвчилсөн, уушиг хэржигнэсэн шуугиантай, нядалсан хонины уушигны эдийн дээжинд эмгэг бие бүтцийн шинжилгээгээр архаг үрэвсэлийн шинж тэмдэгийг оношлов. Мөн архаг үрэвсэлтэй хоёр уушигны эдийн дээжинд (БМЛВ)-ийн gag бүтцийн 536 хос суурь урттай хэсгийг ПГУ-аар илрүүлэн нуклеотидын дарааллыг секвенсингээр баталгаажуулав. Түлхүүр үг: gag, полимеразын гинжин урвал, нуклеотидын дараалал, уушигны архаг үрэвсэл